(untitled) (Medico Legal Update, 2019)
Background/Objectives: This is the descriptive research study to grasp the emotional intelligence, emotional labor and exhaustion of the nurse clinician and using possibility of emotional intelligence in nurse organization by identifying their relationships. Method/Statistical analysis: The data were collected from May till December 2013. The data were collected via structural questionnaires gathered by 230 hospital nurses who consented to take part in the study, and 215 of them were analyzed except for 15 incomplete questionnaires and male nurses. Descriptive statistics, independent t-test, one way ANOVA and Pearson’s correlation were used for analysis. Findings: There were significant nagative correlations of emotional Intelligence with emotional labor(r=-.55, p<.001), and emotional intelligence and exhaustion(r=.31, p=.311),emotional labor and exhaustion(r=.18, p=.002)showed a positive correlation. Improvements/Applications: This study concluded that emotional intelligence of clinical nurses reduce emotional labor and emotional labor increased the exhaustion. Nurses will expect the development of intervention programs to enhance the emotional intelligence of nurses.